ZIKA Virus Neutralizing Antibody Kinetics in Antenatally Exposed Infants. (2nd February 2021) - Espindola, Otavio de Melo; Jaenisch, Thomas; Nielsen-Saines, Karin; Oliveira, Raquel de Vasconcellos Carvalhaes de; Pastorino, Boris; Vasconcelos, Zilton; Gabaglia, Claudia Raja; Ribeiro, Ieda Pereira; Cunha, Denise Cotrim da; Pone, Marcos Vinicius; Carvalho, Liege Maria Abreu de; Pone, Sheila Moura; et al.
Abstract: Background: Zika virus (ZIKV) is associated with severe congenital abnormalities and laboratory diagnosis of antenatal infection is difficult. Here we evaluated ZIKV neutralizing antibody (nAb) kinetics in infants born to mothers with PCR-confirmed ZIKV infection during pregnancy. Methods: Neonates (n = 98) had serum specimens tested repeatedly for ZIKV nAb over the first 2 years of life using virus neutralization test (VNT). ZIKV neonatal infection was confirmed by RT-PCR in blood or urine and/or presence of ZIKV IgM antibodies, and results were correlated with infant clinical features. Results: Postnatal laboratory evidence of ZIKV vertical transmission was obtained for 60.2% of children, while 32.7% exhibited clinical abnormalities. Congenital abnormalities were found in 37.3% of children with confirmed ZIKV infection and 31.0% of children without confirmed infection ( P  = .734). All but 1 child displayed a physiologic decline in ZIKV nAb, reflecting maternal antibody decay, despite an early ZIKV-IgM response in one-third of infants. Conclusions: Infants with antenatal ZIKV exposure do not develop ZIKV nAb despite an early IgM response. Therefore, ZIKV VNT in children is not useful for diagnosis of congenital infection. In light of these findings, it remains to be determined if children infected in utero are potentially susceptible to reinfection. Abstract : Infants with in utero ZIKV exposure do not develop an autochthonous production of anti-ZIKV IgG neutralizing antibodies, even those with confirmed vertical transmission by detection of ZIKV RNA or an early IgM response.